1997
DOI: 10.1021/jf9704571
|View full text |Cite
|
Sign up to set email alerts
|

Aggregate Formation during Hydrolysis of β-Lactoglobulin with a Glu and Asp Specific Protease from Bacillus licheniformis

Abstract: The hydrolysis of isolated β-lactoglobulin (9 and 70−200 mg/mL) by a Bacillus licheniformis protease was followed to assess whether aggregates and gels, respectively, were formed during hydrolysis. Changes during hydrolysis were monitored by electrophoresis, dynamic light scattering, and fluorescence and circular dichroism spectroscopy. Gelation was monitored by dynamic oscillation rheology. Upon hydrolysis of a β-lactoglobulin preparation with the B. licheniformis protease aggregates were formed and a soft g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
2
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 18 publications
6
55
2
1
Order By: Relevance
“…Aggregation of food peptides during enzymatic hydrolysis has been reported earlier (Creusot, Gruppen, van Koningsveld, de Kruif, & Voragen, 2006;Liu & Guo, 2008;Otte et al, 1997;Su, He, & Qi, 2008). The present study further suggested that, at acidic pH values, milk peptides were prone to aggregation caused by the low z-potential and hydrophobic interactions, which led to the formation of covalent bonds among milk peptides.…”
Section: Effect Of Thiol-blocking Agent On Aggregation Of Milk Peptidessupporting
confidence: 84%
See 1 more Smart Citation
“…Aggregation of food peptides during enzymatic hydrolysis has been reported earlier (Creusot, Gruppen, van Koningsveld, de Kruif, & Voragen, 2006;Liu & Guo, 2008;Otte et al, 1997;Su, He, & Qi, 2008). The present study further suggested that, at acidic pH values, milk peptides were prone to aggregation caused by the low z-potential and hydrophobic interactions, which led to the formation of covalent bonds among milk peptides.…”
Section: Effect Of Thiol-blocking Agent On Aggregation Of Milk Peptidessupporting
confidence: 84%
“…The aggregation of milk peptides could occur during enzymatic hydrolysis of whey proteins and caseins (Liu & Guo, 2008;Otte et al, 1997). The self-assembling process of amphiphilic peptides from caseins having a molecular masses of 2e6 kDa was shown to involve chemical interactions such as hydrophobic interactions, H-bond and the cation-p action, leading to the formation of macroaggregates (Liu & Guo, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that enzymatic hydrolysis of β-lactoglobulin can lead to the formation of aggregates, and as a result, gelation occured. 9,10 However, long fibrillar aggregates were not observed in these studies.…”
Section: Introductionmentioning
confidence: 53%
“…It was suggested that the high viscosity was caused by aggregation of the peptides causing a gelation. 27,28 Detailed study of this surprising effect revealed that hydrolysis of the α-lactalbumin fraction by this enzyme in the presence of calcium leads to strong gel formation, 29 and further studies on this gel showed hollow linear filaments similar to microtubules. 25 A very detailed description of the self-assembly of hydrolyzed α-lactalbumin into nanotubes resulted from the work of Graveland-Bikker and is described in her PhD thesis.…”
Section: Viscositymentioning
confidence: 95%